Control of osmotic pressure to improve cell viability in cell‐laden tissue engineering constructs - Carvalho, A. F. (2018)
Design of tissue engineering strategies deals with the need to balance both biomaterials characteristics and techniques specificities, often resulting in cell-compromising processing conditions. One important factor often disregarded is the osmotic pressure to which cells are exposed. An in-house microfluidic system was used to prove that addition of an osmotic regulator significantly benefits the generation of viable cell-laden hydrogels under harsh processing conditions. Human adipose-derived stem cells were resuspended in 1.5% alginate and 1% gellan gum (GG; w/v) solutions containing different concentrations (0.12 m, 0.25 m and 1.5 m) of sucrose as osmotic regulator. GG (in water) and alginate (in water or phosphate-buffered saline) solutions were used to vary the conditions under which cells were kept prior processing. Independently of the polymer, addition of sucrose did not affect the processing conditions or the viscosity of the solutions, except at 1.5 m. The obtained results clearly demonstrate that inclusion of 0.25 m sucrose during processing of the cell-laden hydrogels allowed to keep cell viability around 80%, in opposition to the 20% observed in its absence, both for GG and alginate-derived hydrogels prepared in water. Impressively, the level of cell viability observed with the inclusion of 0.25 m sucrose, 76% for GG and 86% for alginate, was similar to that obtained with the standard alginate solution prepared in phosphate-buffered saline (82%). The beneficial effect of sucrose was observed within the first 5 min of processing and was maintained for prolonged experimental setups with viability values above 50%, even after a 2-h time-frame and independently of the material.